1997
DOI: 10.1108/09684889710165107
|View full text |Cite
|
Sign up to set email alerts
|

A good league table guide?

Abstract: Subjects the league table of universities published in The Times and The Times Good University Guide in 1995 and 1996 to statistical and conceptual analyses. Shows the "measures" used by the compilers of the tables to be problematic in a number of technical respects. Shows that the number of underlying variables is largely reducible to a single factor which discriminates between pre-1992 and post-1992 universities. Casts serious doubt on the validity of the tables from both technical and conceptual perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Finally, there have been numerous analyses of the relevant league tables that have raised questions about their construct validity (Clarke 2002;Eccles 2002;Morrison et al 1995;National Opinion Research Center 1997;Page 1999;Yorke 1997). These include the extent to which the various performance indicators are in fact measuring relevant factors or dimensions of academic quality, whether there is a statistically defensible rationale for the weightings employed in the various league tables, and the legitimacy of constructing rankings when there are not statistically significant differences in the institutional data.…”
Section: Evaluating the League Tablesmentioning
confidence: 98%
“…Finally, there have been numerous analyses of the relevant league tables that have raised questions about their construct validity (Clarke 2002;Eccles 2002;Morrison et al 1995;National Opinion Research Center 1997;Page 1999;Yorke 1997). These include the extent to which the various performance indicators are in fact measuring relevant factors or dimensions of academic quality, whether there is a statistically defensible rationale for the weightings employed in the various league tables, and the legitimacy of constructing rankings when there are not statistically significant differences in the institutional data.…”
Section: Evaluating the League Tablesmentioning
confidence: 98%
“…Also, the assessment of the standing of a particular higher education system and/or higher education institution in this market is again referenced back to HERSs (Hazelkorn 2007;Marginson 2007), often due to a lack of alternative evaluative systems, as in the case of Europe (Federkeil 2008). Thus, HERSs have become established as seemingly unquestioned tools for assessing quality (Federkeil 2008) and university excellence (Taylor and Braddock 2007), for promoting accountability (IHEP 2007), classification (McCormick 2008), comparison (McDonough et al 1998, evaluation (Bellon 2007;Breimer 2007) and information distribution (Bellon 2007;Yorke 1997), as well as for initiating strategy development on the part of higher education systems and higher education institutions (Hazelkorn 2007;Marginson and van der Wende 2007). Consequently, at least as long as ''everyone wants a world-class university'' (Altbach 2003), HERSs ''clearly are here to stay'' (IHEP 2007, p. 2) and ''will continue to be published in ever-increasing numbers'' (Bowden 2000, p. 58).…”
Section: Introductionmentioning
confidence: 95%
“…Other studies have also backed the argument for adaptive and responsive universities. For example, studies focusing on developments within the UK have demonstrated how national rankings led to institutions actively trying to improve their position (Harvey 2008;Yorke 1997).…”
Section: University Rankings-perspectives On Their Impact On Universimentioning
confidence: 99%